Lipid peroxidation, antioxidant enzymes and levels of nitric oxide in sheep infected with Fasciola hepatica - Benzer, F; Ozan, ST (Tubitak Scientific & Technological Research Council Turkey, 2003)
In this study, the levels of malondialdehyde and activities of catalase and glutathione peroxidase, two antioxidant enzymes, and the levels of nitric oxide in sheep infected with Fasciola hepatica were measured. The level of malondialdehyde in plasma and tissue was measured according to the Yagi and Ohkawa methods, respectively. The activities of catalase and glutathione peroxidase were measured according to the methods of Aebi and Beutler, respectively. The level of nitric oxide was determined by the method of Griess. There were no statistically significant differences in the level of plasma malondialdehyde, activities of erythrocytes catalase and glutathione peroxidase and levels of nitric oxide of the group with fasciolasis in comparison with the control group (P > 0.05). However, the level of malondialdehyde in the liver, the activity of catalase and the level of nitric oxide in the group with fasciolasis were much lower than those in the control group while the activity of glutathione peroxidase increased significantly (P < 0.01). Cirrhosis caused by Fasciola hepatica induced significant changes in malondialdehyde and nitric oxide levels and the activities of antioxidant enzymes in liver tissue, though blood parameters were not affected. The fact that blood values were not affected is probably because the damage Fasciola hepatica caused was a mechanical process.
Fasciola hepatica ile enfekte koyunlarda lipid peroksidasyonu, antioksidant enzimler ve nitrik oksit düzeyleri
Keywords: Fasciola hepatica; cirrhosis; malondialdehyde; catalase; glutathione peroxidase; nitric oxide